The relationship between Cycloplegic refraction and age - ســابـق , ياسمينا; تيم درويش ,; قحطـان جلّول , (Latakia University Journal -Medical Sciences Series, 2023)
Purpose: Determining the efficacy of using Cycloplegic Drops to determine the refraction compared to not using it by age. Methods: 151patients (298 eyes) participated in the study, a detailed medical history was taken and information of age and sex was recorded. After obtaining the informed consent, a comprehensive ophthalmological examination was performed, including examination of visual acuity, corrected visual acuity, measurement of refraction by autorefractor, in addition to examination using slit lamp for the anterior sections of the eye and the poseterior sections of the eye. Cyclopentolate 1% was instilled into both eyes 3 times with an interval of 10 minutes, and refraction was measured after 20 minutes from the third time with an Autorefractor device. The sample was divided into age groups. Results: The study found that the difference in refraction before and after cycloplegia remained significant and almost constant at ages up to 30 and then decreased until it disappeared at the age of 50. In patients with myopia, the difference in refraction before and after cycloplegia was (0.52) (0.49) (0.24) (0.13) for age groups (5-20) (20-30) (30-40) (40-50) respectively, and the difference completely disappeared after these ages. As for the patients with Hyperopia, the difference was (0.67) (0.48) (0.35) (0.21)) for age groups (5-20) (20-30) (30-40) (40-50) respectively and the difference completely disappeared after these ages, and we also found in our study that 6% of myopia patients had pseudomyopia and that the difference in the refraction before and after the cycloplegia was greater in hyperopia patients compared to myopia. Conclusion: The difference in refraction before and after cycloplegia is significant and almost constant at ages up to 30 and then decreases until it disappears by the age of 50, although the difference in refraction is greater in hyperopia patients compared to myopia. Keywords: refractometer, cycloplegia, , myopia, hyperopia,